Legendre fractional differential equation and Legender fractional polynomials - Khalil, Roshdi; Abu Hammad, Mamoon (International Journal of Applied Mathematical Research, 2014)
In this paper we study the Legender conformable fractional differential equation. It turns out that in certain cases, similar to the classical case, certain solutions are fractional polynomials. Further, we study basic properties of such fractional polynomials.Keywords: Legendre Fractional Equation, Legendre Fractional Polynomials.